Effect of the PakCat program on nutrition status, dietary pattern and nutrition knowledge and skills of Pakistani women living in Catalonia evaluated by a mixed-method randomized control trial (RCT) - Mohamed-Bibi, Saba; Ribot-Serra, Blanca; Vaqué-Crusellas, Cristina (PLOS ONE, 2025)
Background Pakistani women are among the most affected groups by obesity and heart failure in Catalonia. Due to cultural and linguistic barriers, their participation in standard health promotion programs is limited. To address this issue, we implemented a culturally and linguistically appropriate food education program called the PakCat Program. Methods The study employed a community-based participatory research (CBPR) design, utilizing a two-arm, cluster-assignment, non-blinded mixed-method randomized control trial (RCT) implemented in Badalona and Santa Coloma de Gramenet, two neighboring municipalities with a substantial Pakistani population. Participants were randomly assigned to the control group (n = 67) and the intervention group (n = 70). The intervention group received ten weekly culturally and linguistically appropriate food education sessions over ten weeks, while the control group attended three general sessions. The main outcome measures included nutritional status, nutrition knowledge and skills, dietary patterns, and satisfaction with the intervention, which were assessed pre-and post-intervention combining quantitative methods based on a survey and qualitative approaches consisting of conducting focus group discussions (FGDs). Results The quantitative analysis conducted through a two-factor analysis of variance (ANOVA) for repeated measures indicated a significant improvement in the study variables across the entire sample (p < 0.001 within group), with the intervention group experiencing greater improvements in nutrition knowledge and skills and dietary pattern (p <0.001 for interaction and between groups). These findings were corroborated by thematically analyzed qualitative data confirming a more pronounced improvement in the study outcomes of the intervention group. Furthermore, both groups reported a high level of satisfaction with the intervention. Conclusions The PakCat Program effectively improved the nutrition knowledge, skills, and dietary patterns of immigrant women of Pakistani origin residing in Catalonia. However, future research involving a larger sample size and combining the behavioral and clinical parameters is needed to enhance the generalizability of the results.